(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Three.corrugated.tubes.with various corrugation.depths are.experimentally and numerically. investigated. Air. is used as a working. fluid. in. tube .side. heated .by saturated. steam. passing. through. the. shell. of heat. exchanger where. constant wall temperature. at the. tube side was achieved. The dimensionless corrugation depth (e/Dh) are 0.0216, 0.0469 and 0.0798. However, the corrugation angle (θ) and pitch to diameter ratio (p/Dh) were kept nearly constant of 9ο and 0.5, respectively. The experiments were carried out over the turbulent range of Reynolds number from 5000 to 50,000. The results reveal that the average Nusselt number is increased by 46%, 67% and 105% for corrugation depth ratios of 0.0216, 0.0469 and 0.0798, respectively compared with the smooth tube. However, the average friction factor of the corrugated tube with e/Dh = 0.0216, 0.0469 and 0.0798 are 90%, 135% and 500% higher than of smooth tube, respectively. At the same pumping power, the optimum Nusselt number ratio was 1.4 obtained by corrugated tube with intermediate depth ratio (e/Dh =0.0469). To. visualize the. Flow behavior of flow. inside corrugated. tubes, the numerical.approach.was used.to solve three-dimensional. governing equations. with. shear stress transport k-ω model by using ANSYS, Fluent 15. Solid work was used to generate the physical domain of corrugated tube. The numerical.result showed.that .there is .main vortex. Generated in.the main .flow .due to rotational flow induced .along the helical path. In addition, secondary vortex is originated behind the rib. These .two vortices .can promote .flow .mixing between .the flow.layers.and break.the boundary layer. Consequently, achieve high heat transfer improvement.